(untitled) (Mūzikas akadēmijas raksti, 2024)
During WWII several outstanding Jewish violinists of Latvia perished in ghettos, but in fear of the red terror, almost two thirds of Latvia violinists – pedagogues of Latvia Conservatoire, orchestral musicians and recognized soloists, who were at the peak of their art, left Latvia at the end of WWII (1944). On their arrival in refugee camps in Germany etc., they became part of artists’ groups and started large-scale concert activity, and some chamber ensembles even became popular with foreigners, as many of them gave concerts to German public, too, and to representatives of allied forces. One of the brightest prewar Latvian performing arts young stars, violinist Olafs Ilziņš (1923) chose Venezuela to become his land of settlement and therefore we knew so little about his activities. Work of Olafs Ilziņš did not come into the eye of emigration press, his name is not found in Latvju enciklopēdĳa 1962–1982 created by Edgars Andersons, though this musician was still mentioned in 1951 Latvju enciklopēdĳa edited by Arveds Švābe [8, 790]. The article emphasizes the most important moments in O. Ilziņš creative career; first concerts, that he gave as a child prodigy living in Latvia at the end of 30-ies; concerts after the graduation of Latvia Conservatoire (1940, with honours) at the beginning of 40-ies, receiving many enthusiastic references among foreigners. Performance of O. Ilziņš and other violinists in exile, and their ability to take important place in cultures of foreign countries, clearly show what a loss was suffered by Latvian violin art, the development of which was to be started after the WWII anew on absolutely different principles.